Aging has greater impact on anaerobic versus aerobic power in trained masters athletes - Gent, D. N.; Norton, K. (Journal of Sports Sciences, 2013)
This study measured the relative rates of change of the three human energy systems across a 30-year age range. A cross-section of highly trained masters cyclists (n = 156 males and 17 females; 35-64 years) were tested for maximal cycling performance. There were 50 (29%) track sprint cyclists and the remaining (71%) were predominantly road cycling specialists. A 10 s peak power test measured anaerobic power, a 30 s test measured anaerobic capacity, and a progressive test to volitional fatigue was used to determine peak aerobic power. Participants` exercise patterns were recorded using a physical activity recall questionnaire. Linear regression showed significant changes in anaerobic performance with aging. Peak anaerobic power (W · kg-1) declined at a rate (mean ± SEE) of 8.1 ± 4.1% per decade (P < 0.0001) and anaerobic capacity (kJ/kg) declined at 8.0 ± 3.3% per decade (P < 0.0001). Peak aerobic power [W/kg did not change significantly with age [-1.8 ± 1.5% per decade (P = 0.218)]. This cross-sectional study showed performance of the two anaerobic energy systems declined significantly across the age spectrum with no change in aerobic capacity.